Behavior and foraging technique of the Ingram's squirrel Guerlinguetus ingrami (Sciuridae: Rodentia) in an Araucaria moist forest fragment - Mendes, Calebe Pereira [UNESP]; Cândido Junior, José Flávio (Sociedade Brasileira de Zoologia, 2014)
This work describes the foraging techniques, body positions and behavior of free-ranging Ingram's squirrel Guerlinguetus ingrami Thomas, 1901 in a region of the Araucaria moist forest, in the Atlantic Forest of southern Brazil. The animals were observed using the all occurrence sampling method with the aid of binoculars and a digital camcorder. All behaviors were described in diagrams and an ethogram. We recorded five basic body positions, 24 behaviors, two food choices, and three feeding strategies utilized to open fruits of Syagrus romanzoffiana (Cham.), the main food source of Ingram's squirrels. We also observed a variance in the animals' stance, which is possibly influenced by predation risk, and discuss the causes of some behaviors.
Keywords: Atlantic forest; body position; ethogram; Syagrus romanzoffiana